SEMIOTIC ANALYSIS ON TELEVISION ADVERTISEMENT OF COCA COLA “ REASON TO BELIEVE : INDONESIAN VERSION “ - AYU, SENIA PUSPITA (Jurnal Ilmiah Mahasiswa FIB, 2013)
Advertisement is a medium to deliver messages to people with the goal to influence them to use certain products. Semiotics is applied to develop a correlation within the element used in advertisement. In this study, the writer chooses the television advertisement of Coca Cola “ Reason to Believe: Indonesian Version” as the subject to be analyzed using semiotic study based on Peirce’s theory. Semiotic approach is employed in interpreting the sign, symbol, icon, and index in television advertisements. This study aims to identify: (1) the semiotic signs found in the Coca Cola advertisement, and (2) the interpretation of semiotic signs in the Coca Cola advertisement.This study is qualitative in the form of document analysis. The data are 20 scenes in the Coca Cola “Reason to Believe : Indonesian Version” TV advertisements. The result of this research shows that each advertisement contains semiotic signs such as symbol, icon and index. There are 20 symbols, 46 icons, and 16 index. Icon is mostly used rather than symbol and index. Text are provides as symbol in most scenes. The text use for emphazing the condition of each scene.Suggestion is made for next researchers to choose the signs of the advertisement from other media sources like radio, newspaper, or the internet, to obtain various results. Next researchers can also conduct further studies by seeing people’s interpretation on certain advertisements. Keywords: semiotics, sign, TV advertisement, Coca Cola.